Fenomena K-Pop di Arab Saudi - Ani Mariani (Indonesia Center for Middle East Studies, 2021)
Saudi Arabia is often seen as a very conservative country because of the strong influence of Wahhabism in government, an ideology that tends to be perceived as anti-modernity. The role of the ulama has also been considered very strong in determining state policy. However, since 2016, there have been significant social changes in freedom and leeway granted by the state in various sectors, especially in the social sector. Women are allowed to enter sports stadiums, drive, travel without a guardian. This change also includes providing concessions for entertainment such as music concerts, including what is quite surprising is the entry of the K-Pop phenomenon in Saudi. This policy created debate among various groups, especially among Wahhabi clerics. This article aims to analyze the emerging impact of the social reform process in Saudi Arabia on religious authorities in the country. This study uses a qualitative method by conducting a literature study. This article uses the concept of religious authority and its relation to the digital comunication proposed by Cheong (2011). The results showed that social reform in Saudi Arabia affected the dynamics of religious authority, and there was a shift in authority from traditional authorities, such as ulama, to civil authorities.